Illusion, dream or need - Ayala Montero, Moisés (Avances en Supervisión Educativa, 2013)
“School must get used to, considering the society changes and evolution towards competences and technology.” This is something everybody know, but it does not. A Primary teacher dream show us one experience we can include in that necesary educational change.